Hospital Elder Life Program in Long‐Term Care (HELP‐LTC): A Cluster Randomized Controlled Trial. Issue 10 (25th July 2020) - Boockvar, Kenneth S.; Judon, Kimberly M.; Eimicke, Joseph P.; Teresi, Jeanne A.; Inouye, Sharon K.
Abstract : BACKGROUND/OBJECTIVES: The Hospital Elder Life Program (HELP) has been shown to prevent delirium in hospitalized older adults. The objective of this study was to test the efficacy of HELP adapted to long‐term care (HELP‐LTC). DESIGN: Cluster randomized controlled trial. SETTING: A 514‐bed academic urban nursing home. PARTICIPANTS: A total of 219 long‐term nursing home residents who developed an acute illness or change in condition were randomly assigned to HELP‐LTC (n = 105) or usual care (n = 114) by unit. INTERVENTION: HELP‐LTC is a multicomponent intervention targeting delirium risk factors of cognitive impairment, immobility, dehydration, and malnutrition. Two certified nursing assistants (CNAs) delivered HELP‐LTC components twice daily 7 days per week. In addition, recommendations were given to primary providers to reduce medications associated with delirium. MEASUREMENTS: Delirium (primary outcome) and delirium severity were ascertained each weekday by a research assistant blinded to group assignment, using the Confusion Assessment Method (CAM) and CAM severity score (CAM‐S), respectively. Cognitive function was determined using the Cognitive Performance Scale (CPS). Hospitalization was ascertained by chart review. RESULTS: Participants were 81.7 years of age on average and 65.3% female. At baseline, usual care group participants had better cognitive function than intervention group participants (CPS = 1.33 vs 2.25; P = .004). Delirium symptoms declined over the course of the episode (mean CAM‐S = 3.63 at start vs 3.27 at end). Overall, 33.8% of the total sample experienced incident delirium. After adjusting for baseline cognitive function, no significant differences were found in delirium or delirium severity between intervention and usual care groups. Hospitalization was not significantly different between groups. CONCLUSION: An intervention targeting delirium risk in long‐term nursing home residents did not prevent delirium or reduce delirium symptoms. Baseline differences in cognitive function between groups, greater than expected improvements in both groups, quality‐enhancing practices such as consistent assignments delivered to both groups, and adaptations of the intervention may have biased results toward null. J Am Geriatr Soc 68:2329–2335, 2020.